Ethiopia’s social safety net effective in limiting COVID-19 impacts on rural food insecurity - Abay, Kibrom A.; Berhane, Guush; Hoddinott, John F.; Tafere, Kibrom (International Food Policy Research Institute, 2022)
The COVID-19 pandemic is undermining food and nutrition security on a global scale. IFPRI estimates show that globally, 80–140 million people were at risk of falling into extreme poverty in 2020, more than half in Africa south of the Sahara. The World Food Programme estimated that globally, the number of people facing acute food insecurity could double in the same period. These impacts — stemming from lost incomes due to lockdowns, fear of exposure, and medical expenses, as well as disruptions in food markets and value chains — are severely testing social protection systems in many countries. How effective are those systems in blunting these effects?